2022
DOI: 10.1002/eat.23835
|View full text |Cite
|
Sign up to set email alerts
|

The estimated burden of bulimia nervosa in the Middle East and North Africa region, 1990–2019

Abstract: Objective We aimed to report the burden of bulimia nervosa (BN) in the Middle East and North Africa (MENA) region by age, sex, and sociodemographic index (SDI), for the period 1990–2019. Methods Estimates of the prevalence, incidence, and disability‐adjusted life‐years (DALYs) attributable to BN were retrieved from the Global Burden of Disease study 2019, between 1990 and 2019, for the 21 countries in the MENA region. The counts and age‐standardized rates (per 100,000) were presented, along with their correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Nevertheless, age-specific estimates would be calculated based on the reported sex ratio and uncertainty bounds when the prevalence data were reported for specific age groups without separating by sex, or by sex for large age intervals; (2) The remaining individual sex estimates were performed with MR-BRT. MR-BRT network meta-analysis estimated the pooled sex ratios and uncertainty bounds, which were then adopted to split combined sex estimates and (3) Researches presenting prevalence estimates for age groups of 25+ years were split into 5-year age groups using the age pattern generated by DisMod-MR 2.1 10 13…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, age-specific estimates would be calculated based on the reported sex ratio and uncertainty bounds when the prevalence data were reported for specific age groups without separating by sex, or by sex for large age intervals; (2) The remaining individual sex estimates were performed with MR-BRT. MR-BRT network meta-analysis estimated the pooled sex ratios and uncertainty bounds, which were then adopted to split combined sex estimates and (3) Researches presenting prevalence estimates for age groups of 25+ years were split into 5-year age groups using the age pattern generated by DisMod-MR 2.1 10 13…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to the review, studies that report prevalence were conducted in Nigeria (Ehimigbai et al, 2017), Kenya (Mutiso et al, 2022), Benin (Tognon‐Tchégnonsi et al, 2020), and Burkina Faso (Terhoeven et al, 2020). Additionally, Safiri et al (2022, 2023) estimated prevalence for anorexia nervosa and bulimia nervosa in the Middle East/North Africa region using data from the 2019 GBD study. However, the GBD study imputes its estimates, in this case without any data from epidemiological studies in North African countries (for more information about the GBD methodology see Murray, 2022; Institute for Health Metrics and Evaluation, 2023a).…”
Section: Eating Disorder Epidemiology In African Countriesmentioning
confidence: 99%
“…Moreover, the difficulty in expressing the sense of loss of control could make diagnosing and estimating the prevalence of BED in childhood challenging. Nevertheless, BN and BED appear to be the most prevalent eating disorders, with a lifetime prevalence in adolescents and young adults ranging from 0.8 to 2.6% in BN and 0.6 to 6.1% in BED, and from 0.1–0.16% in BN and from 0.3 to 0.7% in BED, respectively, in girls and boys ( 1 , 48 50 ). In addition, BEDs of lower frequency and/or limited duration are more prevalent.…”
Section: Eating Disorders In Children and Adolescentsmentioning
confidence: 99%
“…Moreover, while challenging the assumption that ED is a phenomenon that mainly affects Western female populations, recent studies have suggested that eating disorders also appear to be a significant global concern ( 57 , 58 ). Disordered eating attitudes have promptly emerged in areas where societies are in transition and where large social and demographic changes are occurring, such as in the Middle East and North Africa, as well as in Eastern Europe, Asia, and Latin America ( 1 , 7 , 50 , 59 , 60 ). This increase can be attributed to many factors, including a better understanding of the pathological conditions, paradigm changes in the expectations people have about their bodies (e.g., body image dissatisfaction when compared to Western fashion), increased demand for mental healthcare, improvements in healthcare systems, and the adoption of a more modern lifestyle, leading to changes in the perception of the “ideal body” ( 50 ).…”
Section: Eating Disorders In Children and Adolescentsmentioning
confidence: 99%